The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1016/j.injury.2016.05.020
|View full text |Cite
|
Sign up to set email alerts
|

Medial Gastrocnemius Flap for Reconstruction of the Extensor Mechanism of the Knee Following High-Energy Trauma. A minimum 5 year follow-up

Abstract: Introduction:

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…Hohmann et al reported three of his four patients has returned to work and sporting activity with a median range of motion from 5-95 degrees. 14 The practice and training of orthopaedic in Malaysia are different from most developed countries. In the United Kingdom, for example, a gastrocnemius flap can only be performed by a plastic surgeon because an orthopaedic surgeon does not have adequate training in this procedure.…”
Section: Discussionmentioning
confidence: 99%
“…Hohmann et al reported three of his four patients has returned to work and sporting activity with a median range of motion from 5-95 degrees. 14 The practice and training of orthopaedic in Malaysia are different from most developed countries. In the United Kingdom, for example, a gastrocnemius flap can only be performed by a plastic surgeon because an orthopaedic surgeon does not have adequate training in this procedure.…”
Section: Discussionmentioning
confidence: 99%
“…Eighteen studies 13,14,[17][18][19][20][21][22][23][24]28,30,33,34 provided information on postoperative rehabilitation following extensor mechanism reconstruction using local flaps. In most cases, patients were placed in either a splint or cast to maintain strict knee immobilization in full extension.…”
Section: Postoperative Carementioning
confidence: 99%
“…Free muscle ap such as latissimus dorsi and gracilis muscle aps has been reported as a reliable alterative approach for reconstruction of the complex tissue defect in the knee region, because of its rich blood supply and large area. 15,16 Those advantages are speci cally indicated more complex soft defects with joint and/or prosthesis exposure. However, problems of donor-site morbidity and bulkiness of aps remain.…”
Section: Disscusionmentioning
confidence: 99%